الاتجاهات الحديثة لإدارة الموارد البشرية في ظل العولمة (دراسة ميدانية في جامعة تشرين) - صيوح, لؤي; ديب, كندة (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research aims to reveal the impact of globalization on human resources management, so as one of the basic challenges facing the contemporary concept of human resource management at the moment. Where it was relying on the literary depth review of previous studies and literature that dealt with the basic concepts of both human resources management and the phenomenon of globalization. The research concluded that there is a significant effect to of global and technological changes, starting knowledge age, and information technology on human resources management strategies, and on the other hand, shows that organizations in general need a radical change in the field of human resources management in order to cope with the phenomenon of globalization and its consequences. The research found a set of recommendations that would give positive support to the human resources management in the face of the negative effects of globalization. هدف البحث إلى الكشف عن تأثير ظاهرة العولمة على إدارة الموارد البشرية وذلك كأحد التحديات الأساسية التي تواجه المفهوم المعاصر لإدارة الموارد البشرية في الوقت الراهن. حيث تم الاعتماد على مراجعة أدبية معمقة للدراسات والأدبيات السابقة التي تناولت المفاهيم الأساسية لكل من إدارة الموارد البشرية وظاهرة العولمة. توصل البحث إلى وجود تأثير معنوي لكل من التطورات التقنية والعالمية، بزوغ عصر المعرفة، تكنولوجيا المعلومات على استراتيجيات إدارة الموارد البشرية، ومن جهة أخرى تبين أن المنظمات بشكل عام بحاجة إلى تغيير جذري في مجال إدارة الموارد البشرية وذلك لمواجهة ظاهرة العولمة ونتائجها. وخلص البحث إلى مجموعة من التوصيات التي من شأنها أن تعطي الدعم الإيجابي لإدارة الموارد البشرية في مواجهة الآثار السلبية لظاهرة العولمة.